2 '-(5-Chloro-2-oxidobenzylidene)benzenesulfonohydrazide-kappa N-2,O 2 '-(2-oxidobenzylidene)benzenesulfonohydrazide-kappa N-2,O copper(II) - Ali, Hapipah Mohd; Ng, S.W.; Rizal, M.R.; Yusnita, J. (International Union of Crystallography, 2007)
The Cu-II atom (site symmetry 1) in the title compound, [Cu(C13H10ClN2O3S)(C13H11N2O3S)], is N, O-chelated by the monoanionic ligands in a trans-CuN2O2 square-planar geometry. The 2'-(2-oxidobenzylidene) benzenesulfonohydrazide anion is disordered equallywith the chlorine-substituted 2'-(5-chloro-2-oxidobenzylidene) benzenesulfonohydrazide anion. An intermolecular N-H center dot center dot center dot O hydrogen bond helps to stabilize the crystal structure.